Abnormal XY interchange between a novel isolated protein kinase gene, PRKY, and its homologue, PRKX, accounts for one third of All (Y+)XX males and (Y-)XY females - Schiebel, Katrin; Winkelmann, Martina; Mertz, Annelyse; Xu, Xiaoling; Page, David C.; Weil, Dominique; Petit, Christine; Rappold, Gudrun (Human molecular genetics, 1997)
Abstract. XX males and XY females have a sex reversal disorder which can be caused by an abnormal interchange between the X and the Y chromosomes. We have isola
Gesehen am 30.03.2021